Level of Knowledge and Awareness of Halitosis in the Dental Medicine Students (Medico Legal Update, 2020)
Background: Halitosis is a general term that means bad odor in the oral cavity that is difficult to treat dueto poor oral health and is a problem affecting 50% of the adult population The impact of halitosis is closelyrelated to the psychological and social effects of a person.Purpose: To find out the level of knowledge and awareness of Dental Medicine Students of UniversitasAirlangga about halitosis and the benefits of the perception and level of awareness of halitosis as a referencein carrying out health promotion.Method: This research will use a cross sectional random sampling study. The survey or questionnaire wasdistributed to 100 students from class of 2014 to 2019 Faculty of Dental Medicine, Universitas Airlangga,Surabaya, Indonesia.Result: The results of this study shows that the level of halitosis knowledge in pre-clinic students showsthat 57% had a proper knowledge and 43% had a poor knowledge. While clinical students have a 46% poorknowledge result and 54% with proper knowledge. For the awareness of halitosis in pre-clinic studentsshows that 91% had a proper awareness and only 9% with poor awareness.Conclusion: The average score of the respondents on poor knowledge of halitosis and poor awareness ofhalitosis, so health promotion that will be carried out can be emphasized on counseling about halitosis.